2018
DOI: 10.1038/s41598-018-35275-w
|View full text |Cite
|
Sign up to set email alerts
|

Density resistance evaluation of maize varieties through new “Density–Yield Model” and quantification of varietal response to gradual planting density pressure

Abstract: Increasing planting density is the main method and key management to enhance the grain yield. Preventing lodging and premature senescence in high planting density, and screening and enhancing the density-tolerance of maize variety is the main goal of agronomy. Differential response of maize hybrids to high plant density greatly affect the dry matter accumulation and its allocation to maize kernel, depending upon various traits responsible for crowding stress tolerance, of which ear characteristics are pivotal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Sher et al, (2017) reported that at higher plant populations, reduced grain yield resulted from increased anthesis-silking interval (ASI) and this is followed by barrenness. The ear-plant height ratio recorded at high density in this study was similar to that reported by Tang et al, (2018). Height of LNTP-W reduced slightly from 148.8cm in ND to 141cm in DD and DDp.…”
Section: Overall Performance Of the Varieties Under Varied Densitiessupporting
confidence: 90%
“…Sher et al, (2017) reported that at higher plant populations, reduced grain yield resulted from increased anthesis-silking interval (ASI) and this is followed by barrenness. The ear-plant height ratio recorded at high density in this study was similar to that reported by Tang et al, (2018). Height of LNTP-W reduced slightly from 148.8cm in ND to 141cm in DD and DDp.…”
Section: Overall Performance Of the Varieties Under Varied Densitiessupporting
confidence: 90%
“…Novacek et al [21] also showed that there are differences between years in yielding performance of genotypes, and Robles et al [20] attributed these differences in year-to-year differentiation of environmental conditions, which were also apparent in our results. Tang et al [22] stated that normalization of density-yield model may remove Genotype x Environment over year interactions for more secure yield estimations, but in our case, the factor interactions were more complex.…”
Section: Yield Estimations and Factor Effectsmentioning
confidence: 65%
“…It was reported that Phellodendron amurense seedlings adapt to shading by reducing stem diameter and seedlings biomass but increase plant height [68]. Additionally, it is also reported that sowing with appropriate density can reduce the lodging risk of maize and winter rapeseed [48,69]. Correlation analysis showed that the stem lodging resistance index was significantly positively correlated with stem diameter and remarkably negatively correlated with plant height under the different planting density as shown in (Figure 10).…”
Section: Lodging Resistance and Stem Morphologymentioning
confidence: 85%